2020
DOI: 10.1186/s12888-020-02901-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of lower 2 h C-peptide and elevated evening cortisol with high levels of depression in type 2 diabetes mellitus

Abstract: Background A number of studies have explored the association between depression and ghrelin, leptin, and cortisol; further, postprandial C-peptide levels have a therapeutic effect on type 2 diabetes mellitus (T2DM). However, the relationship between C-peptide and depression in patients with diabetes, remains unclear. The aim of this study was to explore the association between depression and ghrelin, leptin, cortisol, and C-peptide in patients with diabetes. Methods We enrolled 50 adults without T2DM, 77 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The intervention that is self-efficacy focused is capable of enhancing the self-efficacy of patients, and then further promoting patients to develop and maintain the DSM behaviors. Third, diabetes distress shows a close relation to cortisol or glycemic control, 26 , 27 so the decrease in diabetes distress may be conducive to the patients’ glycemic control by improving the secretion of cortisol. Moreover, the diabetes medications in the 12th month of the 12-month follow-up were also analyzed, and the non-significant difference was identified between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention that is self-efficacy focused is capable of enhancing the self-efficacy of patients, and then further promoting patients to develop and maintain the DSM behaviors. Third, diabetes distress shows a close relation to cortisol or glycemic control, 26 , 27 so the decrease in diabetes distress may be conducive to the patients’ glycemic control by improving the secretion of cortisol. Moreover, the diabetes medications in the 12th month of the 12-month follow-up were also analyzed, and the non-significant difference was identified between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The numerous articles exploring other mechanisms, such as the HPA axis and adipokine, suggest the diversity of mechanisms behind comorbidity. Higher depression severity was found to correlate positively with higher midnight cortisol levels 21 . Patients with diabetes presented the worst glycemia control, the most obese and the worst executive functions, and the reduction of executive functions resulted from depressive symptoms 22 .…”
Section: Introductionmentioning
confidence: 91%
“…The boost in serum corticosterone among diabetic patients and rats suggests that the HPA axis is too active 41–43 . Among patients with T2DM, there was an association between low fasting levels of 2‐h C‐peptide and higher levels of midnight cortisol and higher severity of depression 21 . Research revealed that stressor demands and stress perceptions were associated with depressive symptoms.…”
Section: Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations